2020
DOI: 10.1108/jpcc-11-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

A research model to study research-practice partnerships in education

Abstract: PurposeThis scoping review utilizes findings from 80 articles to build a research model to study research-practice-policy networks in K-12 education systems. The purpose of this study was to generate a broad understanding of the variation in conceptualizations of research-practice-policy partnerships, rather than dominant conceptualizations.Design/methodology/approachArskey and O'Malley's (2005) five stage scoping review process was utilized including: (1) a consultative process with partners to identify resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Recent developments in PLN-related topics, such as research–practice partnerships, have shown that measuring impact is especially challenging under the complex conditions of coproduction [2], wherein multiple stakeholders “aim to shift the research paradigm from one in which the researcher is the sole expert to one in which researchers and stakeholders co-lead research activities and collectively apply their expertise, knowledge and skills within a team” (Hoekstra et al , 2020, p. 2). A scoping review by Cooper et al (2020), for example, found that despite the publication of at least 80 articles on the topic of research–practice partnerships since 2007, only three have provided any guidance about measuring impact. Without robust guidance, stakeholders such as those in PLNs have little recourse to draw comparisons across contexts, to support informed decision-making for increasing the effectiveness and sustainability of interactions or to provide evidence for the impacts of mobilizing knowledge among diverse stakeholders (Davies et al , 2015; Durose et al , 2018; Hoekstra et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in PLN-related topics, such as research–practice partnerships, have shown that measuring impact is especially challenging under the complex conditions of coproduction [2], wherein multiple stakeholders “aim to shift the research paradigm from one in which the researcher is the sole expert to one in which researchers and stakeholders co-lead research activities and collectively apply their expertise, knowledge and skills within a team” (Hoekstra et al , 2020, p. 2). A scoping review by Cooper et al (2020), for example, found that despite the publication of at least 80 articles on the topic of research–practice partnerships since 2007, only three have provided any guidance about measuring impact. Without robust guidance, stakeholders such as those in PLNs have little recourse to draw comparisons across contexts, to support informed decision-making for increasing the effectiveness and sustainability of interactions or to provide evidence for the impacts of mobilizing knowledge among diverse stakeholders (Davies et al , 2015; Durose et al , 2018; Hoekstra et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is often a disconnect between the aims and focus of University-led educational research and priorities of those in practice (Ross & Bruce, 2012;Snow, 2015), described by Snow (2015) as "the science we do and the science we need to improve educational outcomes" (p464). Collaborative research ensures those highly connected to practice (e.g., teachers, school leaders) contribute to the research agenda, making it more likely that practice priorities are fore fronted before research commences (Cooper et al, 2020;Scanlon et al, 1994). Furthermore, participation in research has been shown to improve teachers' attitudes to research and teacher efficacy (Ross & Bruce, 2012) and is argued to democratize the research system, allowing teachers' opportunities to participate in the development of new knowledge (Sjölund et al, 2022a).…”
Section: Benefitsmentioning
confidence: 99%
“…As we create partnerships working at the intersection of research and practice, we can learn, work, and create knowledge together, as well as better understand each other's commitments and constraints (Snow, 2015). Indeed, a defining feature of RPPs is that they are mutually beneficial (Cooper et al, 2020). Baum (2000) warns of being overzealous about RPPs without fully recognizing the time, resources and openness to different perspectives required, in addition to not fully recognizing the potential for disjointed communication or poor-quality outcomes.…”
Section: Benefitsmentioning
confidence: 99%
“…The work environment is everything around the workers that can influence him in carrying out the tasks carried out (Cooper et al, 2020;D'Intino et al, 2020;Mylona & Mihail, 2020;Sarro et al, 2020;Silva-Romo et al, 2020;Velicu & Barca, 2020). The work environment is: "Tools and materials faced, the surrounding environment in which a person works, his working methods, as well as working arrangements both as an individual and as a group" (Apaolaza et al, 2020;Busta & Russo, 2020;Mackert et al, 2020;Pogodziński et al, 2020;Sampson et al, 2020;Susanto, 2020).…”
Section: Work Environmentmentioning
confidence: 99%